Financial Impact of Incentive Spirometry - Adam E. M. Eltorai PhD; Grayson L. Baird PhD; Joshua Pangborn BS; Ashley Szabo Eltorai MD; Valentin Antoci MD, PhD; Katherine Paquette PhD, RN; Kevin Connors BA, RRT, CPFT; Jacqueline Barbaria RRT; Kimberly J. Smeals RRT; Barbara Riley DNP, RN; Shyam A. Patel MD; Saurabh Agarwal MD; et al. (SAGE Publishing, 2018)
Despite largely unproven clinical effectiveness, incentive spirometry (IS) is widely used in an effort to reduce postoperative pulmonary complications. The objective of the study is to evaluate the financial impact of implementing IS. The amount of time nurses and RTs spend each day doing IS-related activities was assessed utilizing an online survey distributed to the relevant national nursing and respiratory therapists (RT) societies along with questionnaire that was prospectively collected every day for 4 weeks at a single 10-bed cardiothoracic surgery step-down unit. Cost of RT time to teach IS use to patients and cost of nurse time spent reeducating and reminding patients to use IS were used to calculate IS implementation cost estimates per patient. Per-patient cost of IS implementation ranged from $65.30 to $240.96 for a mean 9-day step-down stay. For the 566 patients who stayed in the 10-bed step-down in 2016, the total estimated cost of implementing IS ranged from $36 959.80 to $136 383.36. Using national survey workload data, per-patient cost of IS implementation costed $107.36 (95% confidence interval [CI], $97.88-$116.98) for a hospital stay of 4.5 days. For the 9.7 million inpatient surgeries performed annually in the United States, the total annual cost of implementing postoperative IS is estimated to be $1.04 billion (95% CI, $949.4 million-$1.13 billion). The cost of implementing IS is substantial. Further efficacy studies are necessary to determine whether the cost is justifiable.